A Comparative Study of Oxidants on Gold and Silver Dissolution in Acidic Thiourea Solutions - J. C. Huyhua (The Minerals, Metals and Materials Society, 1989)
The effect or various oxidants on gold and silver dissolution in thiourea solutions (0.05 M in H2SO4) was studied using the rotating disc technique, a.t 2s c and 600 rpm. These studies were carried out at constant (4:1) initial molar ratio or thiourea to oxidant concentrations, to produce 50 % thiourea. oxidation. The initial dissolution rate of gold was approximately four times higher in the presence. of ferric sulfate (5.37 x 10-3mg cm-2 s-1) than in the presence of hydrogen peroxide (H2O2), potassium persultate (K2S2O3), or monopersulfa.te (KHS06). The dissolution rates for silver were considerably lower than gold for the same oxidants. Oxidation of thiourea in the presence of peroxygen and persulta.te compounds is a. fast reaction and it is completed in less than ten minutes. On the other hand, the oxidation or thiourea with? ferric.sulfate is slow, yielding a second-order reaction rate constant k = 6.09 I mol-1 h-1. Sulfur formation in the ferric thiourea system begins when ferric ion reduction approaches to completion. With hydrogen peroxide, sulfur is observed at lower thiourea concentration than ferric. Suifate. The presence of a large excess or free thiourea i.e., s to 20 % thiourea oxidation) retards sulfur formation and maintains favorable dissolution rates. Finally, carbon-in-leach experiments indicate that thiourea solutions a.re stable for several days, with ferric sulfate or hydrogen peroxide. The dissolution rates of gold and silver doubles in the presence or activated carbon when hydrogen peroxide is used as oxidant.